PERAN BAITUL HIKMAH DALAM TRANSFORMASI WACANA DAKWAH ISLAMIAH PADA MASA DINASTI ABBASIYAH - Atsni Sudarmansyah, Halwatia Malika; Salsabila, Khalishah; Arsyad, Rifqi Qardhawi; Marpaung, Mustopa; Pratama, Novri; Pane, Afdal Hidayat; Annahlawi, Fazlur Rahman; Windari, Sri (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
This study examines the role of Baitul Hikmah as the main intellectual center in Baghdad during the Abbasid Dynasty and how this institution transformed the discourse of Islamic da'wah. The issue raised is how translation, the development of knowledge, and intellectual discussions at Baitul Hikmah influenced the methods and content of da'wah. Through a historical approach and content analysis, this research traces Baitul Hikmah's contribution to enriching da'wah arguments with philosophy, science, and classical literature. The main findings indicate that Baitul Hikmah not only expanded the scope of Islamic da'wah but also encouraged more open and rational intellectual dialogue. In conclusion, Baitul Hikmah played a vital role in shifting da'wah from a traditional approach to a more inclusive and knowledge-based model.